Some Variables Affecting the Formulation of Oral Loratadine Suspension - Hala S.Yousif; Yehia I. Khalil (College of Pharmacy University of Baghdad, 2017)
Loratadine is a long acting non-sedating anti-histaminic agent that was developed for the treatment of seasonal allergic rhinitis, whose anti-histaminic action is more effective than the other anti-histaminic drugs available commercially. This project was carried out to prepare an acceptable suspension through studying the release of drug in presence of different types and concentrations of suspending agents such as polysorbate 40, xanthan gum, sodium carboxymethylcellulose (NaCMC), aluminum magnesium silicate (veegum) and sodium alginate. The effects of these suspending agents were studied at pH 1.2 (0.1N HCl) and 37 Ù'C. The results showed that the release rate of loratadine in the presence of these suspending agents was dependent on their types and concentrations. The results showed that loratadine release from the formula prepared from xanthan gum is more than that prepared from other polymers in the following order: Sodium alginate < NaCMC < veegum < xanthan gum. However, elegancy of suspension was better on using xanthan gum in a concentration of 0.5%. The obtained results were utilized to formulate 0.1% suspension of loratadine which is physically stable with an optimum drug release. The rheology, sedimentation volume, resuspendability and expiration date were evaluated for the selected formula. The formula that contains loratadine, xanthan gum, glycerol, sorbitol, methyl paraben, propyl paraben, sodium edetate, raspberry flavor at pH 5.0 appears to be a promised formula to be present with estimated shelf life of about 3.8 years. Key word: loratadine, suspension, suspending agent, xanthan gum